2022
DOI: 10.1177/0271678x221145089
|View full text |Cite
|
Sign up to set email alerts
|

CNS-peripheral immune interactions in hemorrhagic stroke

Abstract: Stroke is a sudden and rapidly progressing ischemic or hemorrhagic cerebrovascular disease. When stroke damages the brain, the immune system becomes hyperactive, leading to systemic inflammatory response and immunomodulatory disorders, which could significantly impact brain damage, recovery, and prognosis of stroke. Emerging researches suggest that ischemic stroke-induced spleen contraction could activate a peripheral immune response, which may further aggravate brain injury. This review focuses on hemorrhagic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 144 publications
0
16
0
Order By: Relevance
“…Severe neurological disorders can disrupt this balance and cause various changes in both systems contributing to immune suppression and increased risk of infections. 79,82 Although the underlying mechanisms remain elusive, sympathetic hyperactivity associated with central nervous system injury and activation of the hypothalamus-pituitary-adrenal gland axis have been generally believed as the causes of post-stroke immunosuppression. 79,81,[83][84][85] Sykora et al had demonstrated that autonomic shift with decreased BRS was independently associated with infections during the first 5 days of hospital stay after ICH, and during the first 7 days of hospital stay after ischemic stroke.…”
Section: Immunosuppression and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe neurological disorders can disrupt this balance and cause various changes in both systems contributing to immune suppression and increased risk of infections. 79,82 Although the underlying mechanisms remain elusive, sympathetic hyperactivity associated with central nervous system injury and activation of the hypothalamus-pituitary-adrenal gland axis have been generally believed as the causes of post-stroke immunosuppression. 79,81,[83][84][85] Sykora et al had demonstrated that autonomic shift with decreased BRS was independently associated with infections during the first 5 days of hospital stay after ICH, and during the first 7 days of hospital stay after ischemic stroke.…”
Section: Immunosuppression and Infectionmentioning
confidence: 99%
“…Under normal conditions, the immune system and nervous system interact to maintain physiological stability and balance. Severe neurological disorders can disrupt this balance and cause various changes in both systems contributing to immune suppression and increased risk of infections 79,82 …”
Section: Clinical Significancementioning
confidence: 99%
“…Neutrophil recruitment to and activation in the CNS are associated with formyl peptide receptor 1 (FPR1) expression on microglia and are in fact mediated through IL-1β. The activation of neutrophils by microglia is attenuated by the FPR1 inhibitor T-0080, which reduces cerebral edema and improves neurological function after ICH [ 377 , 378 ]. Similarly, myeloperoxidase (MPO) can mediate the activation of microglia against neutrophils, and MPO knockout can play a beneficial role in the recovery of neurological function after SAH; however, further investigation is needed to determine how these findings can be translated into clinical application [ 379 ].…”
Section: Potential Treatment Strategies and Status Evaluation By Targ...mentioning
confidence: 99%
“…Another study based on human and rat CD163 + BAMs, representing pvMs and mMs, reported a transcriptional change in the acute phase, 16 h after stroke, pointing out a phenotypic shift toward leukocyte chemoattracting gene expression. In line, these BAMs have an impact on BBB permeability via VEGF production, thereby promoting the infiltration of granulocytes [13, 83]. Further phenotypic changes 3 days after stroke included proliferative and inflammatory CD163 + BAMs in rats and higher proliferation of CD169 + BAMs in mice, which were identified in the parenchyma of both species [46].…”
Section: Local Macrophage Respondersmentioning
confidence: 99%
“…In addition, although the depletion of macrophages by clodronate is efficient, it is transient based on the ability of MDMs to replenish their pool. Other limitations of this method are the lack of specificity concerning particular BAM populations and evidence that depletion with clodronate induces inflammation [83]. Whether clodronate also depletes microglia depends on the route of administration and on the use of the mannosylated clodronate liposome variant [13,89,90].…”
Section: Umcmentioning
confidence: 99%